AN ECOLINGUISTIC ANALYSIS OF EBIET G. ADE’S SONG “BERITA KEPADA KAWAN”: REPRESENTATION OF HARMONY BETWEEN HUMANS AND NATURE - Hariati, Puji (UIN Sumatera Utara, 2025)
This study aims to explore the ecological narratives embedded in the lyrics of “Berita Kepada Kawan” by Ebiet G. Ade through the lens of ecolinguistics. Using a qualitative descriptive-interpretative approach, the research analyzes how the song represents the relationship between humans and nature, and how it conveys ecological values through language. The data were drawn from the lyrics of the song and analyzed using Arran Stibbe’s (2015) framework of constructive and destructive ecological discourse. The findings reveal that the song contains strong constructive narratives that promote empathy, spiritual reflection, and environmental responsibility. Nature is not merely portrayed as a backdrop to human suffering, but as an entity deeply intertwined with human emotions and ethical choices. Metaphorical language and symbolic imagery reinforce the urgency of ecological awareness. This study concludes that artistic texts such as songs can serve as powerful mediums for ecological discourse and should be integrated into broader environmental communication strategies. The research contributes to expanding the scope of ecolinguistics by emphasizing the role of music as a tool for environmental education and public awareness.